Designing and evaluating provider results-based financing for tuberculosis care in Georgia: a realist evaluation protocol - Marchal, Bruno (BMJ Open, 2019)
INTRODUCTION: In 2016, Georgian researchers and policymakers were developing a policy to improve the performance of the national tuberculosis (TB) control programme. The research programme ‘Designing and Evaluating Provider Results-Based Financing for Tuberculosis Care in Georgia: Understanding Costs, Mechanisms of Effect and Impact (Results4TB)’ was initiated to inform the policy formulation phase, document the policy implementation and assess the effectiveness, cost-effectiveness and the processes of change. To achieve this, the research team intends to combine an impact evaluation, a cost-effectiveness study and a realist evaluation (RE) within an overarching theory-informed design. This protocol is the RE component of the programme. METHODS: A realist methodological approach will be adopted to guide the research design and evaluation. RE answers the question of ‘what works in which conditions for whom?’ and starts with the development of an initial programme theory (IPT). The IPT will feed into other phases of the realist research cycle (study design, data collection, data analysis and synthesis and theory refinement). Data will be collected in a multiple embedded case study design (five intervention and three control sites) through document reviews, in-depth interviews, non-participant observations and context mapping at facility and national levels. Additional data from other research components (cost-effectiveness and impact evaluation) will aid data triangulation. ETHICS AND DISSEMINATION: The Institutional Review Boards of the National Centre for Disease Control and Public Health in Georgia (ref. IRB # 2018–019) and the Institute of Tropical Medicine, Antwerp (ref. IRB #- 1240/18) have granted ethical approval to the study. TRIAL REGISTRATION NUMBER: ISRCTN14667607